Mempersiapkan Pemimpin Masa Depan yang Anti Korupsi - Khamam Khosiin (JURNAL PUSAKA, 2020)
Corruption issues is not merely about the economical consequences, it is likely more about moral integrity. In this country, almost everyday the news shows us the corruption issues which occurred in the governmental stage. It indicates that our society is still and will always be fight this kind of lack of moral integrity issues. This paper tries to take another perspective about the corruption issue based on the moral aspect, in which it related to the akhlaqul karimah. Akhlaqul karimah is one of moral principles embedded in Muslim’s way of life. Corruption issue is one of moral disease that need to be change by its very root. Therefore, akhlaqul karimah needs to be grounded as early as possible to solve this moral issue problem. Keywords: corruption, moral integrity, akhlaqul karimah.